Seguridad turística que percibe el visitante en la ciudad de Iquitos, 2024 - Casique Cardenas, Alison Alexander (2025)
The purpose of this study was to identify the level of tourist safety that visitors perceive in the city of Iquitos. Uses a quantitative approach, with a goal which is considered fundamental and classified as basic research. In addition, it is a descriptive and not an experimental cross-sectional design. The sample consisted of a group of 150 visitors, both domestic and foreign, from a finite population, with a confidence level of 95% and an error margin of 8%, and a standard deviation of 50. In this study, used simple random probabilistic sampling. The reliability of the instruments was evaluated by using the Cronbach alpha, obtaining a value of 0.901. The perception of visitors about public safety in the city of Iquitos is good, reaching a percentage of 46%, tourist service security is good, 39% percent; information security and facilitation is regular level, 51%; environmental safety is good, reaching 44%. It was found that 64% of the respondents considered that the tourist safety in the city of Iquitos was of a medium level.